Phylogenetic diversity drives soil multifunctionality in arid montane forest-grassland transition zone - Wang, Xiaofei; Gong, Lu; Luo, Yan; Ding, Zhaolong; Guo, Qian; Li, Xiaochen; Ma, Xinyu (Frontiers in Plant Science, 2024)
Exploring plant diversity and ecosystem functioning in different dimensions is crucial to preserve ecological balance and advance ecosystem conservation efforts. Ecosystem transition zones serve as vital connectors linking two distinct ecosystems, yet the impact of various aspects of plant diversity (including taxonomic, functional, and phylogenetic diversity) on soil multifunctionality in these zones remains to be clarified. This study focuses on the forest-grassland transition zone in the mountains on the northern slopes of the Tianshan Mountains, and investigates vegetation and soil characteristics from forest ecosystems to grassland ecosystems to characterize plant diversity and soil functioning, as well as the driving role of plant diversity in different dimensions. In the montane forest-grassland transition zone, urease (URE) and total nitrogen (TN) play a major role in regulating plant diversity by affecting the soil nutrient cycle. Phylogenetic diversity was found to be the strongest driver of soil multifunctionality, followed by functional diversity, while taxonomic diversity was the least important driver. Diverse species were shown to play an important role in maintaining soil multifunctionality in the transition zone, especially distantly related species with high phylogeny. The study of multidimensional plant diversity and soil multifunctionality in the montane forest-grassland transition zone can help to balance the relationship between these two elements, which is crucial in areas where the ecosystem overlaps, and the application of the findings can support sustainable development in these regions.